Analysis of leaf surface and clustering of 10 tree species: a tool in the identification of Amazonian species (Research, Society and Development, 2021)
The objective was to describe and systematize the leaf epidermis of 10 Amazonian forest species, with tools to help the taxonomy, contributing with the technical-scientific knowledge. For this, the usual techniques in plant anatomy were performed, for observation, besides the stomata width, length and frequency and submitted to statistics, applying: Tukey test, ANOVA, Cluster Analysis and Principal Component Analysis. The adaxial and abaxial epidermis cells are heterodimensional, with varying shape and size, rounded and sinuous, in all species the stomata are anomocytic and only Spondias mombin is amphiestomatic, Dipteryx odorata and Virola surinamensis species can be easily Identified due to their guard cell ornamentation, the species Alexa grandiflora and Lecythis lurida have similar structures making identification difficult. The trichomes presented varied forms, being these the best parameter for identification and distinction. The Fabaceae are the ones that have greater structure diversity, making the grouping difficult, the stomatal frequency can be successfully used to group the studied species.